2020
DOI: 10.1101/2020.04.15.035527
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

α-catenin switches between a slip and an asymmetric catch bond with F-actin to cooperatively regulate cell junction fluidity

Abstract: Cell adhesions dynamically tune their mechanical properties during tissue development and homeostasis. Fluid connections required for cell mobility can switch to solid links to maintain the mechanical rigidity of epithelial layers 1,2 . Changes in the composition and clustering of adhesion molecules have been proposed to modulate cell junction fluidity, but the underlying mechanisms are unclear 3,4 . acatenin has been shown to play a fundamental role in different adhesion sites. At adherens cell-cell junctions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Using an improved OT setup and determining the polarity of the filament by measuring the direction of its movement in a separate flow channel containing the pointed (-) end directed motor myosin VI [29], we demonstrated that vinculin itself shows catch bond behavior that is asymmetric: its lifetime bound to F-actin is longer when force is directed towards the pointed (-) end of the actin filament than toward the barbed (+) end [29]. Asymmetric catch bond behavior was also recently reported for aE-catenin alone [35]. We therefore re-measured the forcedependent association of the ternary complex comprising the E-cadherin cytoplasmic domain, b-catenin, and aE-catenin with F-actin (Fig.…”
Section: The Ternary Complex Shows Asymmetric Force-dependent Binding...supporting
confidence: 75%
See 1 more Smart Citation
“…Using an improved OT setup and determining the polarity of the filament by measuring the direction of its movement in a separate flow channel containing the pointed (-) end directed motor myosin VI [29], we demonstrated that vinculin itself shows catch bond behavior that is asymmetric: its lifetime bound to F-actin is longer when force is directed towards the pointed (-) end of the actin filament than toward the barbed (+) end [29]. Asymmetric catch bond behavior was also recently reported for aE-catenin alone [35]. We therefore re-measured the forcedependent association of the ternary complex comprising the E-cadherin cytoplasmic domain, b-catenin, and aE-catenin with F-actin (Fig.…”
Section: The Ternary Complex Shows Asymmetric Force-dependent Binding...supporting
confidence: 75%
“…Structural and biochemical studies [36, 42] found direct contacts between actin-bound αE- catenin ABDs, and suggested that these interactions enhance binding between αE-catenin and F-actin. Cooperative binding of αE-catenin to F-actin was also reported in solution [43] and in a biophysical study wherein a single β-catenin/αE-catenin heterodimer formed a short-lived slip bond, but a higher heterodimer surface density enabled the complex to form a directional catch bond with F-actin [35]. Studies from our laboratories likewise indicate that interactions between neighboring cadherin-catenin complexes facilitates F-actin binding under load [18, 30].…”
Section: Resultsmentioning
confidence: 88%
“…Actin recruitment was found to lead to a significant increase of E-cadherin density (typically between 150% to 200%; Engl et al, 2014;Gao et al 2018;Yonemura et al, 2010). Catenin clustering together with intracellular tension orchestrate a fluid-to-solid phase transition at the membranecytoskeleton interface (Arbore et al, 2020) demonstrating the ability of cells to regulate the rheological properties of their junctional cytoskeleton, independently of myosin activity.…”
Section: Mechanosensation Adapts Actin Cortex Propertiesmentioning
confidence: 99%
“…Speculating on other possible catch bond mechanisms, it is conceivable that by stretching the unstructured tail additional binding sites become available which are concealed in the entangled tail at low forces. Force-enhanced adhesion by unfolding is a common catch bond mechanism (46); examples are the von Willebrand factor (47, 48) and α -catenin bonding to F-actin (49) in the cytoskeleton. In conclusion, an intrinsic catch bond mechanism of Ndc80 complexes is compatible with current knowledge and worth considering as one of the ingredients that define the characteristics of Ndc80 strain stiffening.…”
Section: Discussionmentioning
confidence: 99%